CIPC and LED lights are not effective in controlling sprout growth and development in potato with advanced physiological age - Pedrosa, V. M.D. [UNESP]; da Silva, M. B. [UNESP]; de Oliveira, R. [UNESP]; Carvalho, R. F. [UNESP]; Cecıĺio Filho, A. B. [UNESP]; Teixeira, G. H.A. [UNESP] (International Society for Horticultural Science (ISHS), 2023)
In seed potatoes, low irradiance blue LED light (400-500 nm) has been reported to inhibit sprout growth. Recently, similar effect of low irradiance red (660 nm) and high irradiance far-red LED (735 nm) lights have been reported. However, there is no information regarding the inhibitory effect of LED lights on sprout development in table potato tubers. Therefore, the objective of this study was to evaluate the efficacy of blue, red, and far-red LED lights on sprout development and growth on potatoes with advanced physiological age. Potato tubers of ‘Asterix’ cultivar were harvested at advanced physiological age and cured at 15°C, 95% RH for 15 days. After that, the tubers were submitted to the following treatments: dark (negative control), 20 mg L-1, CIPC (positive control), blue LED light (0.1 µmol m-2 s-1), red LED light (1.0 µmol m-2 s-1), and far-red LED light (1.0 µmol m-2 s-1). The storage was carried out in a cold room at 15°C, 95% RH for up to 30 days. Neither CIPC nor LED light treatments inhibit the sprout development and the number of sprouts (≥2 mm) increased during storage. On the other hand, the LED lights controlled the growth of sprouts, with red and far-red lights being more effective. The color parameter a* was not affected by the treatments, but the b* value reduced on tubers treated with blue and far-red LED lights, probably due to greening. Concluding, CIPC as well as LED lights did not control the development of sprouts in table potatoes at advanced physiological age; however, red and far-red LED lights did control sprout growth similar to seed potatoes.
Keywords: photomorphogenesis; postharvest; quality; Solanum tuberosum L; storage